2016
DOI: 10.1371/journal.pone.0165690
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation within Clonal Lineages of Phytophthora infestans Revealed through Genotyping-By-Sequencing, and Implications for Late Blight Epidemiology

Abstract: Genotyping-by-sequencing (GBS) was performed on 257 Phytophthora infestans isolates belonging to four clonal lineages to study within-lineage diversity. The four lineages used in the study were US-8 (n = 28), US-11 (n = 27), US-23 (n = 166), and US-24 (n = 36), with isolates originating from 23 of the United States and Ontario, Canada. The majority of isolates were collected between 2010 and 2014 (94%), with the remaining isolates collected from 1994 to 2009, and 2015. Between 3,774 and 5,070 single-nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 56 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…It has been suggested that higher mismatch rates among replicates are associated with lower read depth [ 70 ]. For diploid organisms, filtering for minimum read depth from four to seven has been used to reduce error rates [ 25 , 70 ]. For the haploid C .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that higher mismatch rates among replicates are associated with lower read depth [ 70 ]. For diploid organisms, filtering for minimum read depth from four to seven has been used to reduce error rates [ 25 , 70 ]. For the haploid C .…”
Section: Discussionmentioning
confidence: 99%
“…These methods enable sequencing of a targeted genome fraction for a large number of individuals thereby reducing ascertainment bias through simultaneous marker discovery and genotyping [ 12 , 14 ]. Population genomics approaches can improve population genetics studies through generating multitudes of polymorphic markers that better reflect the genome-wide genetic diversity of populations [ 13 , 24 ]; and enhance resolution to identify fine-scale genetic variation [ 25 27 ] or detect rare recombination events [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no vegetative compatibility group was found in Ck (He et al, 1998;Várzea et al, 2002). Clonal populations have been shown to have a demographic advantage not only because of the ability of a single individual to colonize an empty habitat, avoiding the risk of not finding a mating partner, but also because of the ability to produce a large number of offspring and quickly disperse them into an environment to which they are already adapted (Bazin et al, 2014;Dutech et al, 2012Dutech et al, , 2017Hansen et al, 2016). However, the absence of genetic recombination may decrease the adaptation potential in a changing environment, because new genotypes may emerge only by mutation .…”
Section: The Evolutionary and Dispersal Potential Of Ckmentioning
confidence: 99%
“…Depending on coverage, this approach allows for the identification of hundreds to thousands of single nucleotide polymorphisms (SNPs) among a large sample of individuals, thus providing high resolution of genetic differences among individuals. GBS has previously been used in population analyses of plant pathogens to identify novel genetic diversity in high-diversity organisms, identify cryptic sexual recombination among clonal pathogens, and conduct genome-wide-association-studies (GWAS) linking quantitative trait nucleotides (QTNs) with pathogen virulence and mycotoxin production ( Milgroom et al 2014 ; Hansen et al 2016 ; Talas et al 2016 ).…”
mentioning
confidence: 99%